There would be a problem with the formula in your calculation of gravity for the physical spheres.

The correct formula is "P(t) = g * t² **/ 2** + V(t = 0) * t + P(t = 0)",

except I had to do "P(t) = g * t² + V(t = 0) * t + P(t = 0)".

There would be a problem with the formula in your calculation of gravity for the physical spheres.

The correct formula is "P(t) = g * t² **/ 2** + V(t = 0) * t + P(t = 0)",

except I had to do "P(t) = g * t² + V(t = 0) * t + P(t = 0)".

Thanks for the note, I'll pass it on.